Speech Acts of Questioning and Requesting: Politeness and Impoliteness Perspectives - Suhartono, Suhartono (Asa Jurnal Penelitian Pendidikan dan Pembelajaran, 2025)
The shift from face-to-face to digital student-lecturer interactions for thesis supervision, driven by advancements in mobile phone technology, emphasizes the need for students to maintain politeness and avoid impoliteness in directive speech acts, such as questioning and requesting, to foster positive interpersonal dynamics. However, students often exhibit impolite speech acts in these contexts. This study investigates the politeness strategies and impoliteness factors in directive speech acts by students at a private university in Kediri, East Java. Using a pragmatic analysis approach with 'means-end' and 'heuristic' techniques, the study involves compiling, disassembling, reassembling, interpreting, and concluding data from students engaged in thesis consultancy. Findings reveal that students predominantly employ negative politeness strategies over positive ones, with incidental face-threatening acts being more common than accidental or intentional ones. The study highlights implications for students, guiding them to communicate appropriately with lecturers, request actions respectfully, and maintain positive relationships. By understanding these politeness dynamics, students can enhance their communication skills and interpersonal rapport with supervisors in digital academic settings.